2019
DOI: 10.3389/fimmu.2019.00791
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric S100A4 Is Associated With Monocyte Innate Immune Memory and Bypass of Tolerance to Subsequent Stimulation With Lipopolysaccharides

Abstract: Objectives: Most DAMPs in inflammatory diseases are TLR2- and TLR4-ligands and according to the current concept, repeated stimuli would result in tolerance. Aims of the study were to verify this assumption, to investigate whether epigenetic effectors are involved and to explore the situation in rheumatoid arthritis (RA). Methods: A trained immunity (TI) and tolerance protocol was established using peripheral blood monocytes from healthy donors, β-glucan and lipopolysaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Moreover, in a mouse model of atherosclerosis (ApoE −/− mice), short-term treatment of lipopolysaccharide (LPS) in a super-low-dose that mimics chronic infection elicits the polarization of monocytes into a sustained pro-inflammatory state with upregulated Ly6C, CCR5, MCP-1, and decreased SR-B1 expression level, and the result of which is the aggravation of atherosclerosis (27). In addition to microbial stimuli, recent findings demonstrated that several non-microbial endogenous products, which have been associated with ASCVD, can also induce trained immunity in monocytes/macrophages (26,(28)(29)(30). Notably, training of monocytes by these compounds including oxLDL, lipoprotein(a), aldosterone, and the oligomeric S100A4 induces a pro-inflammatory and pro-atherogenic phenotype.…”
Section: Pro-atherogenic Effect Of Trained Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in a mouse model of atherosclerosis (ApoE −/− mice), short-term treatment of lipopolysaccharide (LPS) in a super-low-dose that mimics chronic infection elicits the polarization of monocytes into a sustained pro-inflammatory state with upregulated Ly6C, CCR5, MCP-1, and decreased SR-B1 expression level, and the result of which is the aggravation of atherosclerosis (27). In addition to microbial stimuli, recent findings demonstrated that several non-microbial endogenous products, which have been associated with ASCVD, can also induce trained immunity in monocytes/macrophages (26,(28)(29)(30). Notably, training of monocytes by these compounds including oxLDL, lipoprotein(a), aldosterone, and the oligomeric S100A4 induces a pro-inflammatory and pro-atherogenic phenotype.…”
Section: Pro-atherogenic Effect Of Trained Immunitymentioning
confidence: 99%
“…Notably, training of monocytes by these compounds including oxLDL, lipoprotein(a), aldosterone, and the oligomeric S100A4 induces a pro-inflammatory and pro-atherogenic phenotype. Firstly, the primed monocytes show an enhanced ability of vascular endothelial adhesion and transmigration (28) as well as an increased production of pro-inflammatory cytokines upon re-stimulation by Toll-like receptor (TLR) agonists (26,(28)(29)(30). Besides, the cholesterol-laden foam cell formation and the expression of matrix metalloproteinases, which have been implicated in the progression of atherosclerosis, are both significantly accelerated in oxLDL-trained macrophages (26).…”
Section: Pro-atherogenic Effect Of Trained Immunitymentioning
confidence: 99%
“…Whilst prior LPS exposure can "tolerize" monocytes to future stimulation, we propose that the presence of GM-CSF may prevent or have the opposite effect, driving monocyte "training" to enhance subsequent cytokine responses. Such an effect has recently been shown for S100 proteins in inflammatory arthritis (14).…”
Section: Discussionmentioning
confidence: 55%
“…Macrophages may be tolerant to LPS, an effect that lasts for a period of time. [31] To explore how macrophages become tolerance to LPS, we observed the effects of melatonin and LPS on macrophage polarization. As expected, repeated LPS treatment led to macrophage tolerance of LPS (Fig.…”
Section: Melatonin Reverses the Macrophage Tolerance Of Lpsmentioning
confidence: 99%